Homo economicus in the shortage economy - Hana Lipovská; Lucie Coufalová; Libor Žídek (DANUBE: Law, Economics and Social Issues Review, 2018)
Rational agents react to incentives in the market economy as well as in the centrally planned economy. Economic laws are persistent regardless of the economic system. The legislative system changes the outcome of the game between economic agents and managers. The aim of this paper is to show how rational agents reacted to legislative incentives in the Soviet-type economy in Czechoslovakia in the 1970s and 1980s, that is, how they reacted to the general shortage in the centrally planned economy. Based on the original survey among former managers as well as on the legislative sources from the 1970s and 1980s, a taxonomy was made of economic reactions to the shortage economy. This survey was possibly the last chance to map the experiences of socialist managers who tried to run companies in the centrally planned economy. We distinguish plan manipulation in order to ensure payment bonuses; bribery in order to obtain short-supplied inputs and the creation of reserves for the purpose of fulfilling the plan. It was shown that, if the rational agent wanted to obey the higher law, he was forced to ignore lower legislation.
Keywords: 330; Economic Crimes; Legal Cases; Shortage Economy; State Development Plan; Socialist Enterprises